Derivation of F=FeFp as the continuum limit of crystalline slip. (April 2016) - Reina, Celia; Schlömerkemper, Anja; Conti, Sergio
Abstract: In this paper we provide a proof of the multiplicative kinematic description of crystal elastoplasticity in the setting of large deformations, i.e. F = F e F p, for a two dimensional single crystal. The proof starts by considering a general configuration at the mesoscopic scale, where the dislocations are discrete line defects (points in the two-dimensional description used here) and the displacement field can be considered continuous everywhere in the domain except at the slip surfaces, over which there is a displacement jump. At such scale, as previously shown by two of the authors, there exists unique physically based definitions of the total deformation tensorF and the elastic and plastic tensors F e and F p that do not require the consideration of any non-realizable intermediate configuration and do not assume any a priori relation between them of the form F = F e F p . This mesoscopic description is then passed to the continuum limit via homogenization, i.e. by increasing the number of slip surfaces to infinity and reducing the lattice parameter to zero. We show for two-dimensional deformations of initially perfect single crystals that the classical continuum formulation is recovered in the limit with F = F e F p, det F p = 1 and G = Curl F p the dislocation density tensor.